Environmental and Climate Change Education in Romania from the Perspective of International and National Strategies in the Field - Gabriela-Alina MUREŞAN; Magdalena DRĂGAN (Studia Universitatis Babeş-Bolyai: Geographia)
Environmental and climate change education in Romania from the perspective of international and national strategies in the field. On any society’s way towards sustainable development education plays a fundamental role, by providing knowledge and shaping attitudes. Over the last decades, the education for sustainable development has been increasingly addressed by specific policies at different levels – international, European, national. In this context, this paper aims to briefly review strategies/programs/plans regarding the education for sustainable development at all these levels, with a focus on those in Romania. In order to do this, we surveyed the websites of the UN, the EU, the Ministry of Education and Research of Romania, and read the representative documents on the subject, with the aim of situating developments in the field in Romania in a more general framework, and identifying specific national elements. If internationally, concerns and policies in this field are well-established, in Romania they only date back to the year 2018, as a response to the UN’s 2030 Agenda for Sustainable Development, culminating in 2022 in the development of a strategy for environmental and climate change education. As a way to implement this strategy, the “Green Week” program was introduced in all primary and secondary schools in the country.